Implementation of Problem-Based Learning: Teachers’ and Students’ Perceptions on Learning Impact - Tiara Cahyani; Siti Hamidah; Khoirun Nisa (SCHOOLAR: Social and Literature Study in Education, 2026)
This research aims to analyze teachers’ and students’ perceptions of the Problem-Based Learning (PBL) process, including student engagement, learning experiences, and the impact of students' learning on their abilities. This research employs a qualitative approach using a descriptive method. The research subject consisted of 20 students of the tenth grade at MAN 4 Jombang and a representative teacher, selected using a purposive sampling technique. Data collection technique through in-depth interviews with teachers and students.  The data were analyzed qualitatively through the stages of data reduction, data representation, and conclusions. The results of research show that the implementation of Problem-Based Learning has a positive impact on the learning process. Teachers view PBL as a student-centered learning model that uses context as the basis of learning activities, thereby making students more active in analyzing problems, discussing, and finding solutions. From the student's perspective, PBL is considered more engaging, challenging, and enjoyable compared to conventional learning. In addition to increasing student engagement, PBL also helps develop critical thinking, communication, and collaboration skills, as well as providing a more meaningful learning experience. However, its implementation still faces several challenges, such as limited learning time and some students lacking confidence in discussions. Overall, the Problem-Based Learning model is deemed consistent with the principles of the Merdeka curriculum, which emphasizes student-centered learning.